Social Class and Social Work in the Age of Trump. (2nd April 2020) - Karpman, Hannah; Miller, Josh
ABSTRACT: Social class has many meanings and components – economic, social, political, one's sense of identity, and how class intersects with other social identities – so it is difficult to define it briefly and succinctly. These definitions are further complicated by a global lens, where family of origin, geography, and other factors can pre-determine social class. In this article, we explore the complexities and contradictions of social class in the context of the United States as we believe that this is important for social work, particularly in the age of Donald Trump, where class, and its intersection with race and immigration status, is often used as a weapon to divide society and seek political advantages. While such use of class categories is not new in this country or in political rhetoric globally, the current climate in the United States warrants a review.